University Calculus: Early Transcendentals (3rd Edition)

Published by Pearson
ISBN 10: 0321999584
ISBN 13: 978-0-32199-958-0

Chapter 2 - Section 2.2 - Limit of a Function and Limit Laws - Exercises - Page 67: 51


(a) Quotient Rule. (b) Numerator: Difference Rule - Denominator: Power Rule (c) Numerator: Constant Multiple Rule - Denominator: Sum Rule

Work Step by Step

(a) $$\lim_{x\to0}\frac{2f(x)-g(x)}{(f(x)+7)^{2/3}}=\frac{\lim_{x\to0}(2f(x)-g(x))}{\lim_{x\to0}(f(x)+7)^{2/3}}$$ So from $\lim_{x\to c}\frac{A}{B}$ to $\frac{\lim_{x\to c} A}{\lim_{x\to c} B}$. This is Quotient Rule. (b) $$\frac{\lim_{x\to0}(2f(x)-g(x))}{\lim_{x\to0}(f(x)+7)^{2/3}}=\frac{\lim_{x\to0}2f(x)-\lim_{x\to0}g(x)}{(\lim_{x\to0}(f(x)+7))^{2/3}}$$ - Numerator: $\lim_{x\to c}(A-B)=\lim_{x\to c}A-\lim_{x\to c}B$. This is Difference Rule. - Denominator: $\lim_{x\to c}(A^n)=(\lim_{x\to c}A)^n$. This is Power Rule. (c) $$\frac{\lim_{x\to0}2f(x)-\lim_{x\to0}g(x)}{(\lim_{x\to0}(f(x)+7))^{2/3}}=\frac{2\lim_{x\to0}f(x)-\lim_{x\to0}g(x)}{(\lim_{x\to0}f(x)+\lim_{x\to0}7)^{2/3}}$$ - Numerator: Take a look at $\lim_{x\to0}2f(x)=2\lim_{x\to0}f(x)$. This is Constant Multiple Rule. - Denominator: $\lim_{x\to c}(A+B)=\lim_{x\to c}A+\lim_{x\to c}B$. This is Sum Rule.
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.